2008
DOI: 10.1002/smll.200701251
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Layers of a Semiconducting Polymer via Imprinting and Microwave‐Assisted Grafting

Abstract: Enhancements in both the rate and extent of grafting of poly(9,9'-n-dihexyl fluorene) (PDHF) onto flat and nanopatterned crosslinked photopolymer films are described. Reactivity of the surfaces toward grafting via the Yamamoto-type Ni(0)-mediated coupling reaction is increased by synthesizing and incorporating 2,7-dibromo-9-fluorenyl methacrylate (DBFM, 2) as a new grafting agent. Varying the concentration of surface-embedded DBFM is shown to control both overall graft formation and fluorescence with a maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Yamamoto step-growth polycondensation, [106,107] only thin grafted layers can be formed under harsh reaction conditions, and a predominant quantity of ungrafted polymer forms as well. The surface-initiated polymerization (SIP, or ''grafting-from'') technique usually results in significantly thicker films and can be easily applied to fabricate patterned substrates.…”
Section: Polymer Brushes and Surface Initiated Polymerizationmentioning
confidence: 99%
“…Yamamoto step-growth polycondensation, [106,107] only thin grafted layers can be formed under harsh reaction conditions, and a predominant quantity of ungrafted polymer forms as well. The surface-initiated polymerization (SIP, or ''grafting-from'') technique usually results in significantly thicker films and can be easily applied to fabricate patterned substrates.…”
Section: Polymer Brushes and Surface Initiated Polymerizationmentioning
confidence: 99%
“…The surface grafting of conjugated polymer is a recent field that started in 2004 when Emrick et al showed that CdSe nanocrystals could be integrated into PPV thin films without aggregation . Several techniques have been used via the “grafting through” method to create conjugated brushes, such as Yamamoto, Sonogashira, or Suzuki coupling polycondensations. “Grafting from” has also been developed to graft P3HT via surface‐initiated Kumada catalyst transfer polycondensation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been employed to exploit new materials. As a new heating source, microwave irradiation has been successfully used in a number of chemical approaches to produce many types of nanoparticles, such as metal [23], II–VI group semiconductors [24], oxides [25], vanadium metal-organic frameworks [26], fluoride [27], phosphates [28,29], and even for the grafting of poly(9,90-n-dihexylfluorene) (PDHF) onto flat and nanopatterned crosslinked photopolymer [30]. …”
Section: Introductionmentioning
confidence: 99%